Petrographic characterization of coals of the Semirara formation in Maniguin Wells, Sibay basin, Mindoro-Panay area - Forbes, Monina Tesalona (2004)
The Maniguin area of Sibay Basin, Central Philippines has been regarded to have a high potential to generate large volume of hydrocarbon because of rich source rock. The Lower Claystone Member penetrated by the three exploratory wells drilled in the area was found to be a coal-bearing sequence and identified as the possible source rock. In consideration of the important role played by the maceral compositions of the coal to its potential in generating petroleum, coal petrographywas employed in the study/ Coal facies and sequence stratigraphy were also conducted to determine the paleodepositional environment of the coals. All these were done to identify the factors that caused Maniguin-2, one of the three wells drilled over the Maniguin structure, to yield significant amounts of liquid hydrocarbon...